A Qualified Success? Credit frameworks and lifelong learning - Ralf St. Clair (Adult Education Research Conference, 2024)
Considers the potential of credit and qualifications frameworks to support learners in gaining formal credit for informal and conformal learning. Makes recommendations to increase learner mobility and enhance access and equity.
Keywords: policy; qualifications; equity; access